Mengoptimalkan Kinerja Karyawan Melalui Analisis Pekerjaan yang Sistematis - Dhimas Ari Ardhani; M. Novaldi Putra Ramadan; Wahyu Nurcahyo A; M. Rafi Fajar (Indo Publishing, 2025)
This paper discusses the importance of job analysis in human resource management (HRM) in Islamic educational institutions. This study asserts that a deep understanding of job analysis can help educational institutions to shift from dependence on leader figures to a healthier organizational climate, where each employee has clear job responsibilities. This article covers the definition of job analysis, its purpose, importance, techniques, and the relationship between job analysis and HRM. Job analysis is defined as a systematic process for collecting and analyzing information regarding the duties, obligations, and responsibilities of employees. Its main purpose is to ensure that the workforce can carry out their duties effectively and efficiently. This study also highlights the importance of regular evaluation in developing HR skills and how job analysis results can be used as a basis for managerial decision making. By implementing good job analysis principles, Islamic educational institutions can improve the quality of their management and contribute to the achievement of a better educational vision and mission.